2021
DOI: 10.3390/atmos12020254
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of GPM-Era Satellite Products’ (IMERG and GSMaP) Ability to Detect Precipitation Extremes over Mountainous Country Nepal

Abstract: The reliability of satellite precipitation products is important in climatic and hydro-meteorological studies, which is especially true in mountainous regions because of the lack of observations in these areas. Two recent satellite rainfall estimates (SREs) from Global Precipitation Measurement (GPM)-era—Integrated Multi-Satellite Retrievals for Global Precipitation Measurement (IMERG-V06) and gauge calibrated Global Satellite Mapping of Precipitation (GSMaP-V07) are evaluated for their spatiotemporal accuracy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 81 publications
(148 reference statements)
1
25
0
Order By: Relevance
“…in the north. Being located in the tropical northern limit with diversified topography, the country features a very diverse climate from tropical savanna in low-elevation to polar frost in high-the Himalayas (Karki et al 2015;Nepal et al 2021;Shrestha et al 2021). Annual precipitation is predominately governed by the summer monsoon and westerly winter precipitation (Duncan et al 2013;Ehsan et al 2017;Kansakar et al 2004).…”
Section: Study Areamentioning
confidence: 99%
“…in the north. Being located in the tropical northern limit with diversified topography, the country features a very diverse climate from tropical savanna in low-elevation to polar frost in high-the Himalayas (Karki et al 2015;Nepal et al 2021;Shrestha et al 2021). Annual precipitation is predominately governed by the summer monsoon and westerly winter precipitation (Duncan et al 2013;Ehsan et al 2017;Kansakar et al 2004).…”
Section: Study Areamentioning
confidence: 99%
“…Many scholars have adopted modeling methods [7,8] to simulate the impact of climate change and predict the change on water storage in the coming decades, using remote sensing images, satellite altimetry data, and gravimetry data, such as ICESat/GLAS altimetry data, MSS/TM/ETM plus imagery [9], and GRACE Satellites [10]; though the results obtained from these methods have been limited. However, many recent studies have shown that extensive evaluation of global-scale high-resolution satellite-based rainfall (SBR) products, especially IMERG-V5 and GSMaP-V7 [11][12][13], which can be a good alternative for monitoring daily precipitation, explains the merit of precipitation products in a near-real-time way. Dekai Lu (2018) indicated that accurately measuring light rainfall and winter snow was still a challenging task for the current satellite precipitation retrievals in the paper "Evaluation and Hydrological Utility of the Latest GPM IMERG V5 and GSMaP V7 Precipitation Products over the Tibetan Plateau" [14].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Khan et al (2016) record lower IMERG performance in continental climates with dry summers compared to those with year-round precipitation. Further, performance of IMERG data has been extensively studied in several locations worldwide, where IMERG typically underestimates high intensity rainfall in complex terrain (e.g., Lu et al, 2019;Maggioni et al, 2017;Mayor et al, 2017;Nascimento et al, 2021;Navarro et al, 2020;Nepal et al, 2021;Rojas et al, 2021). Decreased IMERG performance due to orography is a known issue and remains an area for future work (Tan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%